Fundamental studies on the mechanism of action of a novel sirtuin inhibitor (BZD9L 1) in colorectal cancer cells- towards the elucidation of a novel cancer therapeutic agent. - Oon , Chern Ein (Universiti Sains Malaysia, 2016)
Gemcitabine remains the standard treatment for pancreatic cancer. although most patients acquire resistance to the therapy. Up-regulated in pancreatic cancer. SIRTI is involved in tumorigenesis and drug resistance, However the mechanism through which SIRTl regulates drug sensitivity in cancer cells is mainly unknown.